The effect of TERT promoter mutation on predicting meningioma outcomes: a multi-institutional cohort analysis - Groff, Karenna J.; Patel, Ruchit V; Feng, Yang; Ghosh, Hia S; Millares Chavez, Miguel A; O'Brien, Joseph; Chen, William C; Nitturi, Vijay; Save, Akshay V; Youngblood, Mark W; Horbinski, Craig M; Chandler, James P; et al. (The lancet. Oncology, 2025)
Background - Molecular aberrations have been incorporated into tumour classification guidelines of meningioma. TERT-promoter (TERTp) mutation is associated with worse prognosis and is designated a WHO grade 3 biomarker. However, it remains unclear whether TERTp mutation is context-dependent, with other co-occurring genetic alterations potentially driving its association with prognosis. We sought to characterise the role of TERTp mutation in meningioma and guide TERTp sequencing. - Methods - We identified 1492 patients of all ages who had previously received surgery for meningioma across 14 medical centres in the USA, Canada, and Germany. Patients were eligible if they had post-surgical clinical or radiographical assessment of the resection site, and TERTp status evaluated by Nov 1, 2024. Multi-modal profiling was used to assess TERTp mutation, focal gene alterations—including CDKN2A/B loss—and copy number alterations. An adjusted WHO grade was calculated for TERTp-mutant meningiomas, incorporating all WHO criteria except TERTp status. Kaplan-Meier curves and multivariable Cox proportional hazards models were used to quantify the effect of TERTp mutation on the endpoints of overall survival and recurrence-free survival across adjusted WHO grade and co-occurring molecular alterations. - Findings - 64 (4·3%) of 1492 meningiomas were TERTp-mutant and 1428 (95·7%) were TERTp-wildtype. Of the TERTp-mutant meningiomas, 33 (51·6%) were from female patients and 31 (48·4%) were from male patients, and the overall median age was 67 years (IQR 60-75). Of the wildtype meningiomas, 965 (67·6%) were from female patients and 463 (32·4%) were from male patients, and the overall median age of the patients was 59 years (IQR 48-70). Data on race was inconsistently reported and thus excluded. The TERTp-mutant patients had a 5-year overall survival (49·4% [95% CI 33·7-72·4]) and 5-year recurrence-free survival (27·6% [95% CI 16·8-45·5]) resembling that of patients with WHO grade 3 TERTp-wildtype tumours (5-year overall survival 32·3% [95% CI 17·2-60·5], p=0·28, 5-year recurrence-free survival 14·3% [5·8-35·2], p=0·28). However, the TERTp-mutant group had heterogenous histological grading and was enriched for aggressive molecular features, with 1p loss present in 44 (77·2%) of 57 profiled tumours and CDKN2A/B loss in 24 (41·4%) of the 58 profiled tumours. Adjusting tumour grade revealed a subset of TERTp-mutant meningiomas that were more molecularly and clinically benign. Among TERTp-mutant tumours, CDKN2A/B loss played a defining role in stratifying tumour behaviour. Multivariable analysis confirmed this, with CDKN2A/B loss being significantly associated with shorter overall survival (HR 3·04 [95% CI 1·67-5·52], p=0·00026) and faster time to recurrence (HR 5·22 [95% CI 3·10-8·79], p<0·0001), while TERTp-mutation did not independently affect overall survival (HR 1·00 [95% CI 0·53-1·87], p=0·99) or recurrence-free survival (1·17 [95% CI 0·75-1·83], p=0·49). Sequencing for TERTp-mutation demonstrated clinical impact only among histologically WHO grade 2 meningiomas. - Interpretation - The indolent behaviour of certain TERTp-mutant meningiomas suggests that TERTp mutation is not sufficient to assign the most aggressive meningioma grade. Instead, TERT sequencing might offer prognostic utility in identifying high-risk cases among WHO grade 2 meningiomas. - Funding - National Institutes of Health, National Institute of Neurological Disorders and Stroke, Friedberg Charitable Foundation, Courtney Meningioma Research Fund, Fleming Meningioma Research Fund, and the Gray Family Foundation.